2021
DOI: 10.1186/s12968-021-00773-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of cardiovascular magnetic resonance in the prognosis of patients with myocardial infarction with non-obstructive coronary arteries

Abstract: Background It is estimated that 5% to 10% of patients with myocardial infarction (MI) present with no obstructive coronary artery lesions. Until now, most studies have focused on acute coronary syndrome, including different clinical entities with a similar presentation encompassed under the term MINOCA (MI with non-obstructive coronary arteries). The aim of this study is to assess the prognosis of patients diagnosed with true infarction, confirmed by cardiovascular magnetic resonance (CMR), in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…A recent prospective multicenter registry found that late gadolinium enhancement involving 3 or more segments (versus a single segment with late gadolinium enhancement) was associated with triple the risk of major adverse cardiovascular events with CMR performed at a median of 12 days following admission. 38 In contrast, a retrospective study in which CMR was performed at a median of 37 days after presentation reported that cardiomyopathy was associated with worse prognosis (15% mortality at 3.5 years) compared with MI (4% mortality rate at 3.5 years). 39 …”
Section: Role Of Cardiovascular Magnetic Resonance Imaging In Minocamentioning
confidence: 93%
“…A recent prospective multicenter registry found that late gadolinium enhancement involving 3 or more segments (versus a single segment with late gadolinium enhancement) was associated with triple the risk of major adverse cardiovascular events with CMR performed at a median of 12 days following admission. 38 In contrast, a retrospective study in which CMR was performed at a median of 37 days after presentation reported that cardiomyopathy was associated with worse prognosis (15% mortality at 3.5 years) compared with MI (4% mortality rate at 3.5 years). 39 …”
Section: Role Of Cardiovascular Magnetic Resonance Imaging In Minocamentioning
confidence: 93%
“…Similarly, dual antiplatelet therapy was not associated with the risk of MACEs (HR 0.86; 95% CI 0.63-1.18; P = 0.35, I 2 = 21%) among the four studies that enrolled subjects with myocardial infarction with nonobstructive coronary arteries (MINOCA) (Supplementary Fig. S2) [21,31,32,35].…”
Section: Primary Endpointmentioning
confidence: 96%
“…Thirteen published studies [19][20][21][22][23][28][29][30][31][32][33][34][35] with 34,463 patients were enrolled in our meta-analysis. The median follow-up duration was 36 months (range, 12-98 months).…”
Section: Study Selection and Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Thirteen published studies [11][12][13][14][15][20][21][22][23][24][25][26][27] with 34,463 patients were enrolled in our meta-analysis. The median follow-up duration was 36 months (range, 12-98 months).…”
Section: Study Selection and Baseline Characteristicsmentioning
confidence: 99%